Antarctic pack ice algal distribution: Floe‐scale spatial variability and predictability from physical parameters. Issue 14 (29th July 2017) - Meiners, K. M.; Arndt, S.; Bestley, S.; Krumpen, T.; Ricker, R.; Milnes, M.; Newbery, K.; Freier, U.; Jarman, S.; King, R.; Proud, R.; Kawaguchi, S.; et al.
Abstract: Antarctic pack ice serves as habitat for microalgae which contribute to Southern Ocean primary production and serve as important food source for pelagic herbivores. Ice algal biomass is highly patchy and remains severely undersampled by classical methods such as spatially restricted ice coring surveys. Here we provide an unprecedented view of ice algal biomass distribution, mapped (as chlorophyll a ) in a 100 m by 100 m area of a Weddell Sea pack ice floe, using under‐ice irradiance measurements taken with an instrumented remotely operated vehicle. We identified significant correlations ( p < 0.001) between algal biomass and concomitant in situ surface measurements of snow depth, ice thickness, and estimated sea ice freeboard levels using a statistical model. The model's explanatory power ( r 2 = 0.30) indicates that these parameters alone may provide a first basis for spatial prediction of ice algal biomass, but parameterization of additional determinants is needed to inform more robust upscaling efforts. Key Points: First map of the floe‐scale distribution of ice algal chlorophyll a in Antarctic pack ice established Snow depth, ice thickness, and sea ice freeboard levels significantly affect ice algal chlorophyll a distribution Described relationships provide a first step toward upscaling, i.e., predictability of ice algal biomass from sea ice physical parameters